Meningkatkan Hasil Belajar Matematika melalui Penggunaan Bangun Ruang di Kelas VI Sekolah Dasar - Eni Zuriati (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
The background of this study is the low learning outcomes of sixth-grade students in Sekolah Dasar Negeri 04 Sariak Laweh on Math in particular for simple geometry materials. On the basic competency 8.2 about determining the nets of cube and box, the students at the first condition had the lowest score around 50 and the highest was 70 with the average score was 61, 25. In general, the percentage level of mastery learning was just about 18,75%. Therefore, there were many students who have not reached the minimum completeness standard (65 points). The research primary goal is to concretize the learning and involve students in the process of math learning to improve the students’ learning outcomes. The research subject is sixth-grade students in SDN 04 Sariak Laweh. This study conducted in two cycles, from September to October 2017. From the data analysis in the first cycle, it can be reported that the percentage of students’ learning outcomes increased from 18.75% to 81.25%. Based on the data analysis it is generally can be concluded that the learning outcomes experienced an increase significantly in the context of cognitive, psychomotor, and effective. In addition, the teachers are confident to deliver the materials with little weakness, such as time control. In addition, the students also have learning outcome improvement and the students’ are no longer fear and ashamed to answer the questions for the teachers.